The History of Polish Psychotherapy during the Socialist Dictatorship - Aleksandrowicz, Jerzy W. (European Journal of Mental Health, 2009)
The paper presents the history of Polish psychotherapy from 1945 to 1989. Psychotherapy was developed primarily within the framework of psychiatry, under the influence of trends present in the ‘western’ world, due to relatively active international scientific contacts and weak political and ideological limitations. Psychotherapists were instructed in different approaches. The equal rights and position of medical doctors and psychologists – members of the Polish Psychiatric Association Psychotherapy Section – and the domination of the scientific approach in psychotherapy were the Polish specificity. In 1989 the Certificate of Psychotherapist, confirming proper professional qualifications, was introduced.